2020
DOI: 10.3389/ffgc.2020.569184
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Socioeconomic Factors Associated to Deforestation and Forest Recovery in Brazilian Tropical Dry Forests

Abstract: The determination of land cover changes (LCCs) and their association to biophysical and socioeconomic factors is vital to support government policies toward the sustainable use of natural resources. The present study aimed to quantify deforestation, forest recovery and net cover change in tropical dry forests (TDFs) in Brazil from 2007 to 2016, and investigate how they are associated to biophysical and socioeconomic factors. We also assessed the effects of LCC variables in human welfare indicators. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Changes in the land use and land cover context for the domain of TDFs have been reported by several authors [ 23 , 24 , 36 ]. Dupin et al [ 23 ] indicated that between 2000 and 2015 there was a net loss in the order of 3302 km 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Changes in the land use and land cover context for the domain of TDFs have been reported by several authors [ 23 , 24 , 36 ]. Dupin et al [ 23 ] indicated that between 2000 and 2015 there was a net loss in the order of 3302 km 2 .…”
Section: Discussionmentioning
confidence: 94%
“…The dryland forests in other parts of the world like Latin America are increasingly well studied at local, regional, national and continental scale, particularly with regards to carbon/biomass approaches (e.g., sustainable intensification for protected/conservation areas) (Méndez et al 2007, Reynolds et al 2016 and has the most comprehensive forest change/deforestation and biophysical aspects including species population changes, with extensive use of remote sensing (Trejo and Dirzo 2000, Gasparri and Grau 2009, Portillo-Quintero et al 2012, do Espírito-Santo et al 2020. In terms of reviews, many remote sensing reviews are providing valuable information on TDF's biophysical, ecological and socioeconomic at a regional level of Latin America (Castro et Also, reviews of current progress on dryland forests in individual countries can be found in many neotropics countries such as Mexico (Castillo et al 2005, Curry 2020), Venezuela (Fajardo et al 2005, Rodríguez et al 2008, and Costa Rica (Frankie et al 2004, Stoner et al 2004 enabling the identification of knowledge gaps and aiding in the development of a policy-relevant approach to conservation of these forests (Miles et al 2006).…”
Section: Introduction 1tropical Dryland Forestmentioning
confidence: 99%
“…Tropical ecosystems have undergone intense deforestation due to human activities (Silva and Barbosa, 2017;Espírito-Santo et al, 2020;Souza and Reis, 2020). Changes in land cover and use lead to a decrease in biodiversity, compromising ecological regulatory services such as pollination, seed dispersal and biological control (Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological restoration emerges as an important alternative to mitigate part of the negative impacts resulting from human actions (Espírito-Santo et al, 2020;Raupp et al, 2020). The Brazilian Caatinga is the largest remnant of tropical dry forest in South America, which has more than 60% of its area occupied by anthropogenic ecosystems and demand urgent ecological restoration actions (Silva and Barbosa, 2017;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation